Growth performance and fruiting of breadfruit (Artocarpus altilis) clonal plantation at vertic soil area in Gunungkidul, Yogyakarta for conservation strategy. Issue 1 (April 2021) - Adinugraha, H A; Setiadi, D; Santoso, H B; Kartikawati, N K
Abstract: Breadfruit is one of the tree species with a wide distribution in the Indonesian archipelago and shows variations in growth morphology, leave, and fruits. Therefore, the breadfruit clonal test plantation was carried out from several origin distributions at vertisol land in Gunungkidul, Yogyakarta, with a spacing of 5 x 5 m. This study aimed to identify the variation in growth and fruit production of 12 breadfruit cultivars at 10 years old. They were collected from Gunungkidul, Kediri, Banyuwangi, Sukabumi, Banten, Bali, Mataram, Lampung, Bone, Malino, Sorong, and Manokwari. The study was conducted by selecting 4 trees from each cultivar that have average growth and replicated five times. The growth characters of breadfruit trees were observed, namely height, stem diameter at breast height, canopy width, and a number of fruits. The observation results showed that there is a significant influence of origin distribution of breadfruit on growth and fruiting performance. The average tree height was 6.1-9.7 m, stem diameter 14.2-22.0 cm, canopy width 3.2-6.1 m, and the number of ripe fruit 3-21 fruit/tree. Breadfruit clones from South Sulawesi (Bone, Malino) and Papua (Sorong, Manokwari) were relatively stable, showing the best performance in all the characters observed. It is indicated that cultivars from South Sulawesi and Papua were adaptable in vertic soil.